The Border Labyrinth: Information Technologies and Trade in the Presence of Multiple Agencies - Jerónimo Carballo; Alejandro Graziano; Georg Schaur; Christian Volpe Martincus (Inter-American Development Bank (IDB), 2016)
Firms selling products abroad usually have to interact with several border agencies that develop multiple trade regulations and oversee their compliance. These regulations establish the procedures that these firms have to follow and the documents that they have to obtain, fill in, and submit for their exports to be authorized. In this paper, we estimate the effects of introducing information technologies as a new means to complete such traderelated procedures. In particular, we use highly disaggregated firm-level export data from Costa Rica over the period 2007-2013 and exploit the gradual phase-in of an electronic trade single window scheme across groups of products and ports. Results suggest that this new system has been associated with both an expansion in the number of exporting firms and increased firms' exports along the shipment extensive margin and the buyer extensive and intensive margins.
hdl:11319/7691
Keywords: F10; F13; F14; 330; Border Agencies; Information Technologies; Exports; Costa Rica